Fuzzy Neutrosophic Soft Matrices of Type I and Type II. Issue 2 (3rd April 2021) - Uma, R.; Sriram, S.; Murugadas, P.
Abstract : In this paper, two types of fuzzy neutrosophic soft matrix have been introduced and it is shown that the set of all fuzzy neutrosophic soft matrices form a semiring. Further it is explored that the set of all fuzzy neutrosophic soft matrices of both types form a vector space.